Pelatihan Publik Speaking Melalui Pidato Persuasif Siswa Kelas IX Di SMP Negeri 3 Merauke - Wahyuniar; Mudatsir; Ratu Bulkis Ramli; Laurensia Elya Puspita (Yayasan Perguruan Kampus, 2023)
Public speaking is a person's ability to speak in front of an audience or public. The ability to speak in public is not born just like that, but through a continuous process of practice and should be started early, so that one's confidence is more stable. Persuasive speech is one of the means that students can use to practice their ability to speak in public. This activity aims to hone the skills of grade IX students at SMPN 3 Merauke in public speaking through training and mentoring using persuasive speeches. The methods used in this activity are training and mentoring using pre-test, post-test, and direct practice instruments. The result of this activity is to be able to grow students' basic understanding related to public speaking through training activities, as well as provide experience in the form of practice for students through mentoring.